Enjoying Maximising Opportunities For Learning Mathematics - Robin Averill (SEAMEO Regional Centre for QITEP in Mathematics, 2013)
In this keynote we will examine and participate in mathematics teaching and learning practices that contribute to strong learning focussed relationships and enjoyment of mathematics learning. Pedagogies, learning experiences, and caring teacher behaviours that include and extend beyond traditional mathematics teaching practices will be presented as examples of how academic relationships can be fostered towards all students making strong mathematics learning gains. The use of contexts that students find realistic, meaningful, and engaging will be discussed. A culturally responsive mathematics education model that encompasses cognitive, social, physical, and spiritual dimensions will be used to consider themes from the keynote session. Examples of research-practice links will be discussed.